Boron nitride particles and resin composition
Boron nitride particles with controlled size and shape characteristics address the need for low dielectric constant and loss tangent in heat dissipation members, improving thermal conductivity and insulation in electronic devices.
Patent Information
- Application Number
- JP2021558443
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-21
- Filing Date
- 2020-11-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-11-19
AI Technical Summary
Heat dissipation members in electronic devices require low dielectric constant and low dielectric loss tangent characteristics to accommodate increasing signal transmission speeds and capacities, which existing boron nitride particles do not adequately address.
Boron nitride particles with specific average particle diameters (450 nm to 800 nm) and BET diameters (160 nm to 300 nm) and high circularity (0.8 or more) are produced through a controlled manufacturing process, including multiple heating steps with temperature adjustments and gas flow management.
These boron nitride particles enable the creation of heat dissipation members with low dielectric constant and loss tangent, enhancing thermal conductivity and insulation properties.
Smart Images

Figure 0007611845000001
Abstract
Description
[Technical field]
[0001] The present invention relates to boron nitride particles and a resin composition. [Background technology]
[0002] In electronic components such as transistors, thyristors, and CPUs, efficient dissipation of heat generated during use is an important issue. For this reason, heat dissipation materials with high thermal conductivity are used together with such electronic components. Meanwhile, boron nitride particles have high thermal conductivity and high insulation properties, so they are widely used as a filler in heat dissipation materials.
[0003] For example, Patent Document 1 describes a boron nitride agglomerated particle composition that exhibits high thermal conductivity and is very useful for heat dissipation sheets required for power semiconductor devices, etc., and has an average particle diameter (D 50 ) is a composition of boron nitride agglomerated particles having a particle size of 1 μm to 200 μm, and is characterized in that the composition satisfies certain conditions. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-036190 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, devices equipped with electronic components have become faster in signal transmission and have larger capacity, so heat dissipation materials are also required to have properties that contribute to this. Specifically, heat dissipation materials with low dielectric constant and low dielectric loss tangent are desirable.
[0006] Therefore, an object of the present invention is to provide boron nitride particles that can realize a heat dissipation member having a low dielectric constant and a low dielectric tangent. [Means for solving the problem]
[0007] One aspect of the present invention is boron nitride particles having an average particle size of 450 nm or more and 800 nm or less, and a BET diameter of 160 nm or more and 300 nm or less.
[0008] The average circularity of the boron nitride particles may be greater than or equal to 0.8.
[0009] Another aspect of the present invention is a resin composition containing a resin and the above-mentioned boron nitride particles. Effect of the Invention
[0010] According to the present invention, it is possible to provide boron nitride particles that can realize a heat dissipation member having a low dielectric constant and a low dielectric loss tangent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One embodiment of the present invention is boron nitride particles having a specific average particle size and BET diameter. The average particle size reflects the particle size taking into account the agglomeration state of the boron nitride particles (both primary particles and secondary particles). Meanwhile, the BET diameter reflects the particle size of the primary particles of the boron nitride particles. In other words, the boron nitride particles of this embodiment have specific values for both the BET diameter related to the particle size of the primary particles and the average particle size taking into account the agglomeration state (both primary particles and secondary particles).
[0012] The average particle diameter of the boron nitride particles is 450 nm or more, preferably 470 nm or more, 490 nm or more, 510 nm or more, or 530 nm or more, from the viewpoint of reducing the dielectric constant and dielectric loss tangent of a heat dissipation member containing the boron nitride particles (hereinafter also simply referred to as "heat dissipation member"). The average particle diameter of the boron nitride particles is 800 nm or less, preferably 760 nm or less, 720 nm or less, 680 nm or less, 640 nm or less, 600 nm or less, or 560 nm or less, from the viewpoint of improving the dielectric breakdown characteristics of the heat dissipation member.
[0013] The average particle size of the boron nitride particles is measured by the following procedure. Using distilled water as a dispersion medium for dispersing boron nitride particles and sodium hexametaphosphate as a dispersant, prepare a 0.125% by mass aqueous sodium hexametaphosphate solution. Add boron nitride particles to this aqueous solution at a ratio of 0.1 g / 80 mL, and perform ultrasonic dispersion once for 1 minute and 30 seconds at AMPLITUDE (amplitude) 80% using an ultrasonic homogenizer (e.g., manufactured by Nippon Seiki Seisakusho, product name: US-300E) to prepare a dispersion of boron nitride particles. Separate this dispersion while stirring at 60 rpm, and measure the volumetric particle size distribution using a laser diffraction scattering particle size distribution measuring device (e.g., manufactured by Beckman Coulter, product name: LS-13 320). At this time, 1.33 is used as the refractive index of water, and 1.7 is used as the refractive index of boron nitride particles. From the measurement results, calculate the average particle size as the particle size (median diameter, d50) at the cumulative value of 50% of the cumulative particle size distribution.
[0014] The BET diameter of the boron nitride particles may be 160 nm or more, preferably 170 nm or more, 180 nm or more, or 190 nm or more, from the viewpoint of reducing the dielectric constant and dielectric tangent of the heat dissipation member. The BET diameter of the boron nitride particles may be 300 nm or less, preferably 290 nm or less, 280 nm or less, 270 nm or less, or 260 nm or less, from the viewpoint of reducing the dielectric constant and dielectric tangent of the heat dissipation member.
[0015] The BET diameter of the boron nitride particles is a value calculated by the following formula. BET diameter = diameter when 1 g of boron nitride is assumed to be a spherical particle / (BET specific surface area / surface area when 1 g of boron nitride is assumed to be a spherical particle) Where: - Diameter of one spherical particle of boron nitride per gram =(6 / (density of boron nitride particles × π)) 1 / 3 (However, the density of boron nitride particles is 2.26 g / cm 3 (Use -Surface area of 1 g of boron nitride when it is assumed to be one spherical particle =π × (diameter when 1 g of boron nitride is assumed to be one spherical particle) 2 ·BET specific surface area JIS Z 8830 Specific surface area of boron nitride particles measured by single point BET method using nitrogen gas in accordance with ISO 2013.
[0016] The boron nitride particles preferably have a spherical or nearly spherical shape in order to improve the packing property of the boron nitride particles when producing a heat dissipation member and to make the properties of the heat dissipation member isotropic (thermal conductivity, dielectric constant, etc.). From the same viewpoint, the average circularity of the boron nitride particles may preferably be 0.8 or more, 0.82 or more, 0.84 or more, 0.86 or more, or 0.88 or more.
[0017] The average circularity of the boron nitride particles is measured by the following procedure. The image of the boron nitride particle taken with a scanning electron microscope (SEM) (magnification: 10,000 times, image resolution: 1280 x 1024 pixels) is analyzed using image analysis software (e.g., MacView, manufactured by Mountec Co., Ltd.) to calculate the projected area (S) and perimeter (L) of the boron nitride particle. The projected area (S) and perimeter (L) are used to calculate the following formula: Circularity = 4πS / L 2 The circularity is calculated according to the following formula: The average circularity is defined as the average circularity obtained for 100 randomly selected boron nitride particles.
[0018] The boron nitride particles described above can be obtained by a manufacturing method including a first step of reacting a borate ester with ammonia at 750 to 1400°C to obtain a first precursor, a second step of heating the first precursor at 1000 to 1600°C to obtain a second precursor, a third step of heating the second precursor at 1000 to 1600°C to obtain a third precursor, and a fourth step of heating the third precursor at 1800 to 2200°C to obtain a fourth precursor.
[0019] In this manufacturing method, after the second step is completed, the environmental temperature in which the second precursor is placed is temporarily lowered to room temperature (10 to 30°C) before the third step is started. In this way, after heating at 1000 to 1600°C, the temperature is returned to room temperature, and then heating again at 1000 to 1600°C, thereby obtaining boron nitride particles having the above-mentioned characteristics. On the other hand, as a conventional manufacturing method, for example, a manufacturing method including the above-mentioned first step, second step, and fourth step is known, but in the manufacturing method of this embodiment, as described above, the third step is performed in addition to the second step, and the environmental temperature is temporarily lowered to room temperature between the second step and the third step, thereby obtaining boron nitride particles having unprecedented characteristics.
[0020] In the first step, for example, a reaction tube (for example, a quartz tube) installed in a resistance heating furnace is heated to 750 to 1500°C. On the other hand, an inert gas is passed through a liquid borate ester and then introduced into the reaction tube, thereby introducing the borate ester into the reaction tube. On the other hand, ammonia gas is directly introduced into the reaction tube. Examples of the inert gas include rare gases such as helium, neon, and argon, and nitrogen gas. The borate ester may be, for example, an alkyl borate ester, and is preferably trimethyl borate.
[0021] The molar ratio of the amount of ammonia introduced to the amount of borate ester introduced (ammonia / borate ester) may be, for example, 1 or more and 10 or less.
[0022] The introduced boric acid ester and ammonia react in the heated reaction tube to generate a first precursor (white powder). A part of the generated first precursor adheres to the inside of the reaction tube, but most of the first precursor is sent to a recovery container attached to the end of the reaction tube by an inert gas or unreacted ammonia gas and is recovered. The time (reaction time) for reacting the boric acid ester and ammonia is preferably within 30 seconds. The reaction time is the time during which the boric acid ester and ammonia remain in the part (heated part) of the reaction tube heated to 750 to 1400 ° C., and can be adjusted by the gas flow rate when the boric acid ester and ammonia are introduced and the length of the reaction tube installed in the resistance heating furnace (the length of the heated part of the reaction tube).
[0023] In the second step, the first precursor obtained in the first step is placed in another reaction tube (e.g., an alumina tube) installed in a resistance heating furnace, and nitrogen gas and ammonia gas are introduced separately into the reaction tube. The gas introduced at this time may be only ammonia gas. The flow rates of the nitrogen gas and ammonia gas may be appropriately adjusted so that the reaction time is a desired value. For example, the higher the flow rate of ammonia gas, the shorter the reaction time, and as a result, the average particle size of the finally obtained boron nitride particles tends to be larger and the BET diameter tends to be smaller.
[0024] Next, the reaction tube is heated to 1000 to 1600° C. The heating time may be, for example, 1 hour or more and 10 hours or less, thereby obtaining the second precursor.
[0025] After the second step is completed, the power to the resistance heating furnace is turned off, the introduction of nitrogen gas and ammonia gas is stopped, and the temperature inside the reaction tube is lowered to room temperature (10 to 30°C), and the second precursor is allowed to stand still. The standing time may be, for example, 0.5 hours or more and may be 96 hours or less.
[0026] In the third step, nitrogen gas and ammonia gas are introduced into the reaction tube again, and the reaction tube is heated again to 1000 to 1600°C. Examples of the flow rates of nitrogen gas and ammonia gas and the heating time may be the same as those described in the second step. The conditions of the second step and the third step may be the same or different from each other. This results in the third precursor.
[0027] In the fourth step, the third precursor obtained in the third step is placed in a boron nitride crucible and heated to 1800 to 2200°C in a nitrogen atmosphere in an induction heating furnace. The heating time may be, for example, 0.5 hours or more and 10 hours or less. This allows the boron nitride particles having the above-mentioned properties to be obtained.
[0028] The boron nitride particles described above are suitable for use in, for example, heat dissipation members. By using the above-mentioned boron nitride particles, a heat dissipation member with a low dielectric constant and a low dielectric loss tangent can be obtained. When the boron nitride particles are used in a heat dissipation member, they are used as a resin composition mixed with, for example, a resin. That is, another embodiment of the present invention is a resin composition containing a resin and the above-mentioned boron nitride particles.
[0029] The content of the above-mentioned boron nitride particles, based on the total volume of the resin composition, is preferably 30 vol. % or more, more preferably 40 vol. % or more, and even more preferably 50 vol. % or more, from the viewpoint of improving the thermal conductivity of the resin composition and making it easier to obtain excellent heat dissipation performance, and is preferably 85 vol. % or less, more preferably 80 vol. % or less, and even more preferably 70 vol. % or less, from the viewpoint of suppressing the generation of voids during molding and the deterioration of insulation and mechanical strength.
[0030] Examples of resins include epoxy resins, silicone resins, silicone rubber, acrylic resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyolefins (polyethylene, etc.), polyimides, polyamideimides, polyetherimides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyesters, polysulfones, liquid crystal polymers, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins.
[0031] The resin content may be 15 vol.% or more, 20 vol.% or more, or 30 vol.% or more, and may be 70 vol.% or less, 60 vol.% or less, or 50 vol.% or less, based on the total volume of the resin composition.
[0032] The resin composition may further contain a curing agent that cures the resin. The curing agent is appropriately selected depending on the type of resin. For example, when the resin is an epoxy resin, the curing agent may be a phenol novolac compound, an acid anhydride, an amino compound, or an imidazole compound. The content of the curing agent may be, for example, 0.5 parts by mass or more or 1.0 parts by mass or more, and 15 parts by mass or less or 10 parts by mass or less, relative to 100 parts by mass of the resin.
[0033] The resin composition may further contain boron nitride particles other than the above-mentioned boron nitride particles (for example, known boron nitride particles such as chunky boron nitride particles formed by agglomeration of scaly primary particles). EXAMPLES
[0034] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0035] [Examples 1 to 3] Boron nitride particles were prepared by the following procedure. First, in the first step, a reaction tube (quartz tube) installed in a resistance heating furnace was heated to the temperature shown in Table 1. On the other hand, nitrogen gas was passed through trimethyl borate and then introduced into the reaction tube, thereby introducing trimethyl borate into the reaction tube. On the other hand, ammonia gas was directly introduced into the reaction tube. The molar ratio of the amount of ammonia introduced to the amount of trimethyl borate introduced (ammonia / trimethyl borate) was set to 4.5. As a result, trimethyl borate and ammonia were reacted to obtain a first precursor (white powder). The reaction time is as shown in Table 1.
[0036] In the second step, the first precursor obtained in the first step was placed in another reaction tube (alumina tube) installed in a resistance heating furnace, and nitrogen gas and ammonia gas were separately introduced into the reaction tube at the flow rates shown in Table 1. The reaction tube was then heated at the temperature and for the time shown in Table 1. As a result, a second precursor was obtained.
[0037] Next, the power to the resistance heating furnace was turned off, the introduction of the nitrogen gas and the ammonia gas was stopped, and the temperature inside the reaction tube was lowered to 25° C., and the second precursor was left to stand for 2 hours.
[0038] Subsequently, in the third step, nitrogen gas and ammonia gas were again introduced into the reaction tube at the flow rates shown in Table 1, and the reaction tube was again heated at the temperature and for the time shown in Table 1. In this way, a third precursor was obtained.
[0039] In the fourth step, the third precursor obtained in the third step was placed in a boron nitride crucible and heated in an induction heating furnace under a nitrogen atmosphere at the temperature and for the time shown in Table 1. Thus, boron nitride particles were obtained.
[0040] [Comparative Example 1] Boron nitride particles were obtained in the same manner as in Example 1, except that the third step was not carried out.
[0041] The average particle size, BET diameter, and average circularity of each of the obtained boron nitride particles were measured by the following methods. The results are shown in Table 1.
[0042] (Average particle size) Distilled water was used as a dispersion medium for dispersing boron nitride particles, and sodium hexametaphosphate was used as a dispersant to prepare a 0.125% by mass aqueous solution of sodium hexametaphosphate. Boron nitride particles were added to this aqueous solution at a ratio of 0.1 g / 80 mL, and ultrasonic dispersion was performed once for 1 minute and 30 seconds at AMPLITUDE (amplitude) 80% using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, product name: US-300E) to prepare a dispersion of boron nitride particles. The dispersion was taken while stirring at 60 rpm, and the volume-based particle size distribution was measured using a laser diffraction scattering particle size distribution measuring device (manufactured by Beckman Coulter, product name: LS-13 320). At this time, 1.33 was used as the refractive index of water, and 1.7 was used as the refractive index of boron nitride particles. From the measurement results, the average particle size was calculated as the particle size (median size, d50) at the cumulative value of 50% of the cumulative particle size distribution.
[0043] (BET diameter) The BET diameter was calculated according to the following formula. BET diameter = diameter when 1 g of boron nitride is assumed to be a spherical particle / (BET specific surface area / surface area when 1 g of boron nitride is assumed to be a spherical particle) Where: - Diameter of one spherical particle of boron nitride per gram =(6 / (density of boron nitride particles × π)) 1 / 3 (However, the density of boron nitride particles is 2.26 g / cm 3 (Use -Surface area of 1 g of boron nitride when it is assumed to be one spherical particle =π × (diameter when 1 g of boron nitride is assumed to be one spherical particle) 2 ·BET specific surface area JIS Z 8830This is the BET specific surface area of boron nitride particles measured by the BET single point method using nitrogen gas in accordance with ISO 2013.
[0044] (Average circularity) First, the projected area (S) and perimeter (L) of the boron nitride particle were calculated by image analysis using image analysis software (e.g., MacView, manufactured by Mountec Co., Ltd.) for an image of the boron nitride particle (magnification: 10,000 times, image resolution: 1280 x 1024 pixels) taken using a scanning electron microscope (SEM). Next, the projected area (S) and perimeter (L) were calculated using the following formula: Circularity = 4πS / L 2 The circularity was determined according to the following formula: The average value of the circularities determined for 100 randomly selected boron nitride particles was calculated as the average circularity.
[0045] The dielectric constant and dielectric loss tangent of each of the obtained boron nitride particles were measured by the following method. The results are shown in Table 1. The boron nitride particles were mixed with polyethylene (product name "Novatec HY540" manufactured by Japan Polyethylene Co., Ltd.) in an amount such that the boron nitride particles constituted 20 volume % and then formed into a sheet having a thickness of 0.2 mm. The mixing and sheet forming were carried out using a twin-screw extruder at a temperature of 180°C. The sheet obtained was measured using a cavity resonator method measuring device at a frequency of 36 GHz and a temperature of 25°C to determine the dielectric constant and dielectric loss tangent of the sheet.
[0046] [Table 1]
Claims
1. Boron nitride particles having an average particle size of 450 nm or more and 800 nm or less, a BET diameter of 160 nm or more and 300 nm or less, and an average circularity of 0.8 or more.
2. A resin composition comprising a resin and the boron nitride particles according to claim 1.
Citation Information
Patent Citations
Granulated powder, resin composition for heat radiation, heat radiation sheet, semiconductor device, and heat radiation member
JP2016074546A
Boron nitride aggregated particle composition, BN aggregated particle-containing resin composition and their compact, as well as production method of boron nitride aggregated particle
JP2017036190A
Hexagonal crystal boron nitride powder and method for producing the same, and composition and heat dissipation member using the same
JP2019116401A